2023
DOI: 10.3389/fneur.2023.1179673
|View full text |Cite
|
Sign up to set email alerts
|

Effects of esketamine on postoperative rebound pain in patients undergoing unilateral total knee arthroplasty: a single-center, randomized, double-blind, placebo-controlled trial protocol

Abstract: IntroductionRebound pain, transient and acute postoperative pain after the disappearance of regional block anesthesia, has been a concern in recent years. Insufficient preemptive analgesia and hyperalgesia induced by regional block are the main mechanisms. At present, the evidence for the treatment of rebound pain is limited. The esketamine, as an antagonist of the N-methyl-D-aspartate receptor, has been proven to prevent hyperalgesia. Therefore, this trial aims to evaluate the impact of esketamine on postoper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…This single-center, prospective, double-blind, randomized, placebo-controlled, pragmatic study will assess our hypothesis that elderly patients treated with S-ketamine will have a lower risk of POD. We have reason to believe that S-ketamine can significantly reduce postoperative pain scores and opioid consumption, which would be consistent with our previous findings ( Zhu et al, 2023 ). We have reviewed the literature to identify potential preoperative confounding variables, including age, ASA class, education level, comorbidities, electrolyte disturbances, malnutrition, smoking and drinking, history of falls, visual and auditory disorders, depression, dementia, functional status, frailty, and sleep disturbances.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This single-center, prospective, double-blind, randomized, placebo-controlled, pragmatic study will assess our hypothesis that elderly patients treated with S-ketamine will have a lower risk of POD. We have reason to believe that S-ketamine can significantly reduce postoperative pain scores and opioid consumption, which would be consistent with our previous findings ( Zhu et al, 2023 ). We have reviewed the literature to identify potential preoperative confounding variables, including age, ASA class, education level, comorbidities, electrolyte disturbances, malnutrition, smoking and drinking, history of falls, visual and auditory disorders, depression, dementia, functional status, frailty, and sleep disturbances.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, elderly patients with preoperative dementia, depression, and multiple comorbidities will be included, making the dose of S-ketamine received in the intervention group more conservative. Our previous study found that subjects receiving 0.3 mg/kg/h S-ketamine had hallucinations and dreaminess, although this dose was subanesthetic (Zhu et al, 2023). Therefore, we will use a smaller subanesthetic dose of S-ketamine 0.2 mg/kg infused over 1 h in this trial.…”
Section: Interventionsmentioning
confidence: 99%
“…Local infiltration injections of periarticular medications are also a type of regional block that may lead to postoperative transient rebound pain. The mechanism of rebound pain is unknown, and it may be relatively sudden nociceptive pain due to inadequate analgesia or hyperalgesia caused by regional blockade [ 28 , 29 ]. Other factors may include neurotoxicity of the local anesthetic, withdrawal reactions, potential pain facilitation, and personal or surgical factors.…”
Section: Discussionmentioning
confidence: 99%
“… 22 , 23 However, this study found no statistically significant difference in the occurrence of postoperative nausea and vomiting between the two groups, which is consistent with domestic and international studies. 19 , 24 , 25 Furthermore, a meta-analysis on the use of esketamine for postoperative acute pain also indicated that esketamine does not reduce the incidence of postoperative nausea and vomiting. 26 Another consideration when using esketamine during the perioperative period is the occurrence of psychiatric adverse reactions such as hallucinations, nightmares, and delirium.…”
Section: Discussionmentioning
confidence: 99%